Pengaruh Keamanan, Kemudahan, dan Pengalaman Berbelanja Terhadap Minat Beli Ulang Secara Online Pada Tokopedia (Studi Kasus Mahasiswa FEB Universitas Islam Malang) - Rozacky, Gilang Ahmad Nur; Rachma, N.; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Technology has progressed so rapidly that it has changed people's lifestyles in carrying out daily activities. Generally, in this technological era, people tend to choose to fulfill their needs by shopping online at e-commerce. The main function of e-commerce is to facilitate interaction, simplify marketing activities and promote products by sellers and simplify the online payment process for consumers.This study aims to determine and analyze the effect of security, convenience and shopping experience on online repurchase interest on Tokopedia. The research method used is quantitative research where variables are measured using a Likert scale and processed using the SPSS 25 application. The population in this FEB student at the Islamic university of malang. The sample used amounted to 95 respondents with data collection using a questionnaire. The research results show that security, convenience and shopping experience simultaneously influence online repurchase interest. Security partially influences online repurchase interest, convenience partially influences online repurchase interest and partial shopping experience influences online repurchase interest. Keywords: Security, Convenience, Shopping Experience and Repurchase Interest.